A Critical Review of the Literature on Structural Adjustment and the Environment - Gueorguieva, Anna; Bolt, Katherine (World Bank, Washington, DC, 2014)
This paper analyzes the available literature about the effects of structural adjustment programs (SAPs) on the environment and the convincing evidence for their success or failure. The studies covered refer to the SAPs by the World Bank as well as to general government programs that have similar policy implications. SAPs are designed to reform economies to become more liberalized and export-oriented while reducing the role of governments that have become inefficient bureaucracies. Because of the implications of policies such as debt accumulation and trade, a concise literature review on debt and trade liberalization is also included. Despite the controversy surrounding structural adjustment and the environment, the debate has been largely based on anecdotal evidence and country case studies. Most of the studies reviewed are not quantitative and have not applied rigorous statistical methods. The conclusions of studies on the effects of structural adjustment (SA) on the environment are strongly influenced by what is examined, the sectoral level, and the stage of the SA process. The infrequency of high-caliber studies is due to data scarcity and statistical limitations. There is little reason to doubt, however, that over the longer term, the sorts of changes in incentive structures and relative price changes brought about by SA lending will have an impact on the environment. Economies undergoing SA will experience both growth (assuming the success of SAPs) and structural shifts, which will affect the extraction of natural resources and the level of pollution emissions.